Loop‐mediated isothermal amplification (LAMP) assays for Anopheles funestus group and Anopheles gambiae complex species. Issue 3 (10th March 2020) - Kamber, T.; Koekemoer, L. L.; Mathis, A.
Abstract: Species of the genus Anopheles vary with regard to their vector capacity for Plasmodium spp., the causative agent of malaria, and their accurate identification is often required. Loop‐mediated isothermal amplification (LAMP) is a rapid, simple and low‐cost method for specific DNA amplification. Primers for LAMP assays specific for the Anopheles funestus group and Anopheles gambiae complex species as well as for the species Anopheles arabiensis, An. funestus, An. gambiae s.s / Anopheles coluzzii (major vectors) and Anopheles rivulorum (minor vector) were designed targeting specific genome or rDNA internal transcribed spacer regions. Reaction conditions (buffer composition, primer concentrations, incubation time) were evaluated and the specificities of the assays confirmed with DNA from non‐target Anopheles species. DNA release from the mosquitoes is achieved simply by heating them for 5 min in water. An aliquot of the DNA solutions is transferred to the reaction tube using disposable inoculation loops. The outcome of the LAMP amplifications after 1 h incubation at 65 °C can easily be visualized by a colour change visible to the naked eye. The assays are operable under field conditions requiring only basic equipment (portable heat block programmable at 65 and 80 °C, cooler for master mixes). Abstract : Loop‐mediated isothermal amplification assays for the Anopheles funestus group, the Anopheles gambiae complex species and for the species Anopheles arabiensis, An. funestus, An. gambiae s.s/ Anopheles coluzzii and Anopheles rivulorum were designed. Reaction conditions (buffer composition, primer concentration, incubation time) were evaluated and the specificities of the assays confirmed with DNA from non‐target Anopheles species. The assays are operable under field conditions requiring only basic equipment (e.g. portable heat block, cooler for master mixes).